(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical characteristics, serum progesterone levels, and evaluate the correlation between these factors and pregnancy outcomes in In Vitro Fertilization (IVF) patients experiencing vaginal bleeding in the first 12 weeks at the National Center for Reproductive Support. Subjects and Methods: A prospective descriptive observational study conducted on 67 IVF patients with vaginal bleeding symptoms during the first 12 weeks of pregnancy, monitored from 07/2024 to 04/2025. Results: A total of 67 IVF pregnancies complicated by vaginal bleeding during the first 12 weeks were included in the study. The mean maternal age was 31.85 ± 5.00 years, and the prevalence of overweight/obesity in the study population was 41.79%. Mild vaginal bleeding accounted for 94.03% of cases. Subchorionic hematoma detected on ultrasound was common, with a prevalence of 70.15%. The mean serum progesterone level in the study group was 57.59 ± 31.98 nmol/L. Among the patients, 5.97% had progesterone levels below 15 nmol/L, 23.88% had levels between 15–30 nmol/L, and 70.15% had levels above 30 nmol/L. Serum progesterone levels were associated with first-trimester pregnancy outcomes.. Conclusion: Vaginal bleeding during the first trimester in IVF pregnancies is a common symptom, most frequently presenting as mild bleeding. The mean serum progesterone level in the study population was 57.59 ± 31.98 nmol/L.